Improving physical self-perception and health-related fitness through gamification in physical education: A cluster randomized controlled trial - Ferdinando Cereda (Physical Education and Sports: Studies and Research, 2026)
Background: The global decline in adolescent physical activity necessitates pedagogical innovation to counter disengagement. Traditional norm-referenced physical education (PE) often alienates less skilled students, whereas gamification offers a promising criterion-referenced strategy to enhance motivation and learning. Objectives: This study investigated the efficacy of a 12-week gamified didactic intervention on perceived physical self-concept, health-related fitness, and physical activity enjoyment among high school students. Methods: A two-arm, parallel-group, cluster randomized controlled trial (Cluster-RCT) was conducted with 210 Italian adolescents (mean age 15.4 ± 0.9 years) nested within 10 intact classes (average cluster size = 21). Intact classes were randomised to an experimental group (gamified ‘MoveQuest’ module, k = 5) or a control group (traditional direct instruction, k = 5). Data were collected using the Revised Physical Self-Perception Profile (PSPP-R-IT), the ALPHA-FIT test battery, and the Physical Activity Enjoyment Scale (PACES). Following a per-protocol analytical approach, Linear mixed models (LMMs) were employed to analyse the data, accounting for the nested structure of the educational setting and handling cluster-level variance intraclass correlation coefficients (ICCs). Significance levels were interpreted considering the multiplicity of outcomes. Results: Significant group × time interactions were observed, with the gamified group demonstrating superior improvements in sports competence (d = 0.65), physical self-worth (d = 0.58), and enjoyment (d = 0.82) compared to the control group. Physiologically, the experimental group showed significantly greater gains in cardiorespiratory fitness (V̇O₂ max) and agility, while body attractiveness remained stable in both groups. Conclusions: Gamified didactics significantly enhance psychological engagement and specific motor performance parameters by prioritising individual progress over social comparison. This approach represents a valuable pedagogical tool for fostering physical literacy in secondary PE.